EXAMINING THE RELATIONSHIP BETWEEN PERCEIVED DIFFICULTY, READING SELF-EFFICACY, AND DISCUSSION TEXT COMPREHENSION OF GRADE XII EFL STUDENTS - marpaung, syafaruddin; Manugeren, M; Suhadi, Jumino; Siwi, Purwanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
This study investigates Grade XII EFL students' perceived reading difficulty, reading self-efficacy, and comprehension of discussion texts from the government textbook Life Today. Guided by Cognitive Load Theory (to interpret perceived difficulty), Bandura’s self-efficacy framework (to examine confidence and persistence), and Barrett’s taxonomy (to structure literal, inferential, and evaluative comprehension), the study addresses three research questions: (1) What features of the Life Today discussion texts do students perceive as most difficult? (2) How do students describe their reading self-efficacy when engaging with these texts? and (3) How is comprehension demonstrated across literal, inferential, and evaluative levels? A qualitative descriptive design was employed at SMA Negeri 2 Kota Tanjungbalai, Indonesia. Thirty-six Grade XII students completed Written Comprehension Responses (WCR) aligned with Barrett’s levels, and fifteen students were purposively selected through maximum variation sampling for in-depth Think-Aloud Protocol (TAP) sessions and Semi-Structured Interviews (SSI). Data were collected sequentially (TAP–WCR–SSI) and analyzed using thematic analysis with directed coding supported by a transparent codebook and intercoder agreement procedures. Findings indicate that perceived difficulty clusters around tracking pro–contra arguments, processing academic vocabulary, interpreting contrastive cohesion markers, and generating inferences when conclusions are implicit. Students’ self-efficacy was relatively strong in persistence but weaker in evaluating arguments and justifying judgments with textual evidence. Comprehension patterns revealed stable literal understanding, whereas inferential and evaluative performance frequently weakened when students struggled to integrate claims, reasons, and evidence across paragraphs. The study highlights the importance of psychologically informed scaffolding such as argument mapping, explicit cohesion instruction, and mastery-oriented feedback to strengthen higher-order comprehension and reading confidence in textbook-based argumentative tasks.